Development of a metal sieve-linked double syringe liquid phase microextraction method for the determination of copper in olive leaf extract samples by flame atomic absorption spectrometry - Gosterisli, Tugce Unutkan; Kublay, Irem Zehra; Oflu, Sude; Kilinc, Yagmur; Kocoglu, Elif Seda; Zaman, Buse Tugba; Keyf, Seyfullah; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2022)
This work reports the development of a simple, sensitive and low-cost analytical method for the trace determination of copper. A metal sieve-linked double syringe liquid phase microextraction method was used to preconcentrate copper into measurable quantities for FAAS system. The pressurized mixing offered by the automated syringe system and the sieve connector enhanced surface area for analyte and extraction solvent interaction, this significantly increased the extraction efficiency for copper. There was therefore no need for auxiliary organic solvents as disperser solvents for the extractant dichloromethane. The limits of detection and quantification, linear dynamic range and percent relative standard deviation values calculated for copper under optimum conditions of the method were 1.5 and 5.1 mu g L-1, 5.0-500 mu g L-1 and 8.4%, respectively. The developed method was successfully employed to determine copper (0.75-8.06 mg kg(-1)) in unspiked olive leaf samples.
Keywords: Copper; Flame atomic absorption spectrometry; Liquid phase microextraction; Dichloromethane; Olive leaf; Sieve-linked double syringe; PRECONCENTRATION; WATER; FOOD; Chemistry; Food Science & Technology; Nutrition & Dietetics